Religieuse Kommunikasie: ter Omskrywing van ’n Ontluikende Akademiese Dissipline (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
Religious Communications, a largely underdeveloped academic discipline, is in this article compared with the academic discipline of Spirituality, which has recently experienced strong growth. Shared characteristics of these two subject areas are indicated, after which the thoroughly interdisciplinary nature of the discipline of Religious Communications is pointed out.